2020
DOI: 10.3390/ijms21082901
|View full text |Cite
|
Sign up to set email alerts
|

Red Chinese Cabbage Transcriptome Analysis Reveals Structural Genes and Multiple Transcription Factors Regulating Reddish Purple Color

Abstract: Reddish purple Chinese cabbage (RPCC) is a popular variety of Brassica rapa (AA = 20). It is rich in anthocyanins, which have many health benefits. We detected novel anthocyanins including cyanidin 3-(feruloyl) diglucoside-5-(malonoyl) glucoside and pelargonidin 3-(caffeoyl) diglucoside-5-(malonoyl) glucoside in RPCC. Analyses of transcriptome data revealed 32,395 genes including 3345 differentially expressed genes (DEGs) between 3-week-old RPCC and green Chinese cabbage (GCC). The DEGs included 218 transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 84 publications
(109 reference statements)
1
22
0
Order By: Relevance
“…The scale bar is 4.5 cm. purple Chinese cabbage, interspecific-crossing between a green Chinese cabbage and a red cabbage was used, combined with recurrent backcrossing to acquire red aneuploid individuals of Chinese cabbage (Lee et al, 2018), for which a series of upregulated ABGs were reported (Rameneni et al, 2020). Unlike those breeding approaches, we relied on the intersubspecificcrossing between a white head Chinese cabbage and a purple flowering Chinese cabbage, with the control of the key BrMYB2 gene located on chromosome A07 (He et al, 2016(He et al, , 2020b.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The scale bar is 4.5 cm. purple Chinese cabbage, interspecific-crossing between a green Chinese cabbage and a red cabbage was used, combined with recurrent backcrossing to acquire red aneuploid individuals of Chinese cabbage (Lee et al, 2018), for which a series of upregulated ABGs were reported (Rameneni et al, 2020). Unlike those breeding approaches, we relied on the intersubspecificcrossing between a white head Chinese cabbage and a purple flowering Chinese cabbage, with the control of the key BrMYB2 gene located on chromosome A07 (He et al, 2016(He et al, , 2020b.…”
Section: Discussionmentioning
confidence: 99%
“…The red or purple germplasm of Chinese cabbage has been well discussed when adopting different conceptions of breeding via hybridization ( Zhang et al, 2016 ; Lee et al, 2018 ; He et al, 2020b ). Among them, Zhang et al (2016) created a purple head Chinese cabbage by crossing a common Chinese cabbage with a red color B. juncea using the embryo rescue technique and continuous backcrossing, in which the purple genes were translocated onto chromosome A02; in another breeding case of purple Chinese cabbage, interspecific-crossing between a green Chinese cabbage and a red cabbage was used, combined with recurrent backcrossing to acquire red aneuploid individuals of Chinese cabbage ( Lee et al, 2018 ), for which a series of upregulated ABGs were reported ( Rameneni et al, 2020 ). Unlike those breeding approaches, we relied on the intersubspecific-crossing between a white head Chinese cabbage and a purple flowering Chinese cabbage, with the control of the key BrMYB2 gene located on chromosome A07 ( He et al, 2016 , 2020b ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations